LL-VNS attenuates SK2 expression and incidence of arrhythmias following acute myocardial infarction in rats - Chen, Mingxian; Zhu, Tongjian; Wu, Zhihong; Hu, Lin; Wu, Zhijian; Liu, Qiming; Zhou, Shenghua (Frontiers in Cardiovascular Medicine, 2023)
Objectives We previous study demonstrated that low-level vagus nerve stimulation (LL-VNS) protected heart against ventricular arrhythmias (VAs). However, its potential mechanisms ventricular electrophysiology properties still remained unknown. Methods Forty-five rats were divided into three groups: Control group (sham AMI following sham LL-VNS, N=15), AMI group (AMI following sham LL-VSN for 60 mins, N=15), and AMI+LL-VNS group (AMI following LL-VSN for 60 mins, N=15). Heart rate variability (HRV), ventricular effective refractory period (ERP), ventricular fibrillation threshold (VFT), and left stellate ganglion (LSG) were measured. Finally, myocardial tissues were collected for tissue analysis. Results AMI directly induced hyperactivity of LSG and reduced vagal tone according to HRV. AMI decreased VFT, shortened ERP but increased ERP dispersion. AMI resulted in loss of ventricular small-conductance Ca2+-activated K+ (SK2) expression and disordered localization. However, LL-VNS significantly abolished the effects of AMI. Conclusions LL-VNS altered ventricular electrophysiological properties through inhibiting cardiac sympathetic nervous activity and reduced SK2 expression.